2008
DOI: 10.1017/s104161020800714x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of drug use on fall incidents among nursing home residents: a systematic review

Abstract: Research on the contribution of psychoactive drugs to fall risk in nursing home residents with dementia is limited. The scarce evidence shows, however, that multiple drugs, antidepressants and anti-anxiety drugs increase fall risk in nursing home populations with residents with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 38 publications
1
53
0
7
Order By: Relevance
“…To date, there have been several systematic reviews conducted on patients in acute or chronic care hospitals, [8][9][10] on the elderly, 11,12 or on nursing home residents. 13 However, patients in psychiatric setting have been largely neglected in fall prevention research; despite the fact that fall is also a major safety concern in psychiatric units. It has been reported that the fall rate in psychiatric unit is comparable to those of elder care and rehabilitation units, with a fall rate of 91 per 1000 admissions compared to 115 and 85 per 1000 admissions respectively for elder care and rehabilitation units.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been several systematic reviews conducted on patients in acute or chronic care hospitals, [8][9][10] on the elderly, 11,12 or on nursing home residents. 13 However, patients in psychiatric setting have been largely neglected in fall prevention research; despite the fact that fall is also a major safety concern in psychiatric units. It has been reported that the fall rate in psychiatric unit is comparable to those of elder care and rehabilitation units, with a fall rate of 91 per 1000 admissions compared to 115 and 85 per 1000 admissions respectively for elder care and rehabilitation units.…”
Section: Introductionmentioning
confidence: 99%
“…For eldre, spesielt i sjukeheimar, er fall eit stort helseproblem (7,8). Ofte er det dårleg balanse og ustø gange som fører til falla, og i tillegg kan medikamentbruk og demens auke fallrisikoen (8).…”
Section: Introduksjonunclassified
“…Likevel veit vi lite om korleis dose og varigheit for medikamentbruk påverkar fallrisikoen. Litteraturen om relativ påverknad av dei ulike legemiddelklassane er heller ikkje klår (8). Det er vist at legemiddel som diuretika, type Ia antiarytmika, digoxin og psykotropiske medikament, aukar fallrisikoen, og at desse har samanheng med fallrate (9)(10)(11)(12)(13).…”
Section: Introduksjonunclassified
See 1 more Smart Citation
“…While risk factors for falls include advanced age, cognitive disorders, hearing and visual disorders, osteoarthritis of the knee, medications (sedatives, hypnotics, neuroleptics, anti-psychotics and antidepressants, non-steroidal antiinflammatory drugs, antihypertensives), presence of any daily life difficulties, living conditions in general population, disease-specific symptoms are added to them in PD (8)(9)(10)(11). Patients with PD who are at risk of falling may have problems with various areas of movement control, such as sensory integration, functioning with a narrow base of support, controlling their centerof-mass movement within their base of support, and coordination of anticipatory postural control tasks (4,12) as well as comorbid conditions (eg, peripheral neuropathy) and medication side effects (eg, postural hypotension and dyskinesia) (13).…”
mentioning
confidence: 99%